Improving the Accuracy of Krill Target Strength Using a Shape Catalog - Fiona Bairstow; Sven Gastauer; Luke Finley; Tom Edwards; C. Tom A. Brown; So Kawaguchi; Martin J. Cox (Frontiers in Marine Science, 2021)
Antarctic krill are subject to precautionary catch limits, based on biomass estimates, to ensure human activities do not adversely impact their important ecological role. Accurate target strength models of individual krill underpin biomass estimates. These models are scaled using measured and estimated distributions of length and orientation. However, while the length distribution of a krill swarm is accessible from net samples, there is currently limited consensus on the method for estimating krill orientation distribution. This leads to a limiting factor in biomass calculations. In this work, we consider geometric shape as a variable in target strength calculations and describe a practical method for generating a catalog of krill shapes. A catalog of shapes produces a more variable target strength response than an equivalent population of a scaled generic shape. Furthermore, using a shape catalog has the greatest impact on backscattering cross-section (linearized target strength) where the dominant scattering mechanism is mie scattering, irrespective of orientation distribution weighting. We suggest that shape distributions should be used in addition to length and orientation distributions to improve the accuracy of krill biomass estimates.

The Role of the Dental Community in Oropharyngeal Cancer Prevention Through HPV Vaccine Advocacy - Thomas Luke Arnell; Collin York; Alexis Nadeau; Maeve Lauren Donnelly; Laura Till; Pedram Zargari; Wendy Davis; Christine Finley; Thomas Delaney; Jan Carney (Journal of Cancer Education, 2021)

The krill maturity cycle: a conceptual model of the seasonal cycle in Antarctic krill - So Kawaguchi; Toshihiro Yoshida; Luke Finley; Paul Cramp; Stephen Nicol (Polar Biology, 2007)